2009
DOI: 10.1016/j.jebo.2009.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Career concerns incentives: An experimental test

Abstract: Holmström's (1982/99) career concerns model has become a workhorse for analyzing agency issues in many fields. The underlying signal jamming argument requires players to use information in a Bayesian way, which is difficult to directly test with field data: typically little is known about the information that individuals base their decisions on. Our laboratory experiment provides prima facie evidence: i) the signal jamming mechanism successfully creates incentives on the labor supply side; ii) decision errors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…In both settings, the principal's earnings were based on the agent's ability and not on his performance. Koch et al (2009) reported that, consistent with the theoretical prediction, an agent's effort is greater when his abilities are hidden. Moreover, and also consistent with theoretical predictions, the wages that the agent receives from the principal are correlated with the effort level when the ability is unknown, but not when the ability is known.…”
Section: Related Literaturesupporting
confidence: 63%
See 1 more Smart Citation
“…In both settings, the principal's earnings were based on the agent's ability and not on his performance. Koch et al (2009) reported that, consistent with the theoretical prediction, an agent's effort is greater when his abilities are hidden. Moreover, and also consistent with theoretical predictions, the wages that the agent receives from the principal are correlated with the effort level when the ability is unknown, but not when the ability is known.…”
Section: Related Literaturesupporting
confidence: 63%
“…Testing the classic career concerns model, Koch et al (2009) reported on a laboratory experiment that compared a setting in which the principal observes the sum of the effort and ability to a setting in which the principal observes the two variables separately. In both settings, the principal's earnings were based on the agent's ability and not on his performance.…”
Section: Related Literaturementioning
confidence: 99%
“…Career-concerns models have been applied mostly to the compensation of CEOs and other senior executives, beginning with Fama (1980). We are aware of two experimental papers on career concerns; the more recent (Koch, Morgenstern and Raab 2009) is actually the simpler one. Consider a world with a finite number of agents and principals.…”
Section: B) Career Concernsmentioning
confidence: 99%
“…For their experiments, Irlenbusch and Sliwka (2006) as well as Koch, Morgenstern and Raab (2009) used a simplified two-period version of the well-known career-concerns model by Holmström (1982Holmström ( , 1999. The two experimental papers yield mixed results on the validity of career concerns for real decision makers.…”
Section: Introductionmentioning
confidence: 99%